The Olympic Games in Paris (2024) and the Greek Cypriot Sport Press: The Views of Newspapers ‘O Phileleftheros’ and ‘Haravgi’ - Antoniades, Euripides; Dimosthenous, Evripidis (My University, 2025)
The Olympic Games in Paris represent the most significant sporting event worldwide. This paper examines how the Greek Cypriot press covered the 2024 Summer Olympics, with a particular focus on how the Games are depicted in the two Greek Cypriot daily newspapers with the highest circulation: O Phileleftheros and Haravgi. More specifically, relying on the theories of framing and agenda settings and using content analysis, the paper researched: a) the analytic way which the two newspapers cover the Olympic Games in Paris (July 26 - August 11, 2024) and b) how the participation and especially the successes of Cypriot and Greek athletes were reported in the press. Olympic medalists Pavlos Kontides and Miltiadis Tentoglou stand out as emblematic athletes of these Games, celebrated and elevated to hero status through media coverage. On the one hand, O Phileleftheros newspaper supports the efforts of Greek athletes and publishes sports news in its sports magazine describing their participation and performance. On the other hand, Haravgi newspaper provides news coverage of the Olympic Games. In conclusion, the paper highlights the role that the newspapers played during the Olympic Games, reflecting society’s needs to receive sports-related news, amid global conflicts and developments.
Keywords: O Phileleftheros; Haravgi; Olympic Games; Press